Isolation and photophysical properties of Di- and Tri-substituted natural anthraquinones from Malaysian Morinda citrifolia - Nabila Elyana Adnan,; Nur Atiqah Mohd Nasuha,; Zanariah Abdullah,; Choo, Yeun-Mun; Hairul Anuar Tajuddin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Five di- and tri-substituted natural anthraquinones, i.e. nordamnacanthal (1), damnacanthal (2), rubiadin (3), 1-methoxy-2-methyl-3-hydroxyanthraquinone (4) and 1-hydroxy-3-methoxyanthraquinone (5) were subjected to photophysical studies. The results indicated that steric hindrance and intramolecular hydrogen bonding are important factors that affect absorption and emission spectral of these natural anthraquinones. Besides that, emission properties were significantly enhanced with formation of intramolecular hydrogen bonding in 1,3-dihydroxy-2-aldehyde tri-substituted anthraquinone 1. This gave rise to formation of two additional quasi aromatic rings extending the π-conjugation system in the anthraquinone structure.